Penggunaan Composit Resin pada Kasus Resisi Gingiva - S. Suryono (Faculty of Dentistry, Universitas Gadjah Mada, 2012)
Background: The clinical appearance of gingival tissue play an essential role in aesthetics. Gingival morphology and color effect on the aesthetic concerns for the patient. Gingival recession can cause exposure of the underlying rootsurface and hypersensitive of the tooth. Purpose: this case reports showed the treatment of gingival recession by using gingival-shaded composite. Case and treatment: Exposed root surface is layered by gingival-shaded composite and its also improved aesthetics by replacement of the restoration. Conclusion: The use of gingival-shaded composite in the area of exposed root surface for layering improved the aesthetic and relief the sensitive denting of patient.